Hungary : Report on the Observance of Standards and Codes (ROSC)-Data Module-Substantive Update on the Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2004)
This Report on the Observance of Standards and Codes (ROSC) data module provides a substantive update on the assessment of Hungary's government finance statistics against the Special Data Dissemination Standard, complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. Significant improvements in addressing the shortcomings identified in the original ROSC data module have been made. These improvements relate mainly to the institutional coverage of general government, consolidation of data, and so on. Significant progress has also been made toward the adoption of the Government Finance Statistics Manual 2001 framework.